(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The History of Economic Sanctions in International Law: exploring the use of economic pressure measures as a tool of foreign policy from ancient times to the present day. The article examines the evolution of the legal framework of sanctions, their effectiveness, and their impact on international relations. Particular attention is paid to the role of international organizations (League of Nations, UN) and key judicial decisions that have shaped the legality and legal implications of sanctions. The article also discusses contemporary challenges and trends in the field of sanctions, including issues of human rights compliance and humanitarian consequences.